2018
DOI: 10.1111/ijfs.13835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound treatment and concentration of ethanol on selectivity of phenolic extraction from apple pomace

Abstract: Summary The extraction of polyphenols from apple pomace was studied using ultrasound, ethanol/water mixtures and moderate temperatures, 20–37 °C. The extraction kinetics and extraction yields of catechin and total phenolic content (TPC) were evaluated at different times of ultrasound treatment (tu) and concentrations of ethanol (Ce). The highest extraction efficiency of TPC was observed at tu = 30 min, Ce = 50% and total extraction time of te = 60 min. The high selectivity of catechin extraction was demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
(32 reference statements)
4
16
0
3
Order By: Relevance
“…Kumari, Tiwari, Hossain, Rai, and Brunton () investigated the ultrasound‐assisted extraction of polyphenols from potato peels; they observed that time showed a significant positive effect on the extent of bioactive extraction and the rate of extraction was higher at the start of extraction time. Wang, Boussetta, Lebovka, and Vorobiev () observed that the initial portions of extracts was richer in catechin content as compared with last portions of extracts obtained using the long duration of ultrasound‐assisted extraction in ethanol/water mixtures. The previous literatures indicated that the extraction time is an important factor for the extraction of ingredients from plant materials.…”
Section: Resultsmentioning
confidence: 99%
“…Kumari, Tiwari, Hossain, Rai, and Brunton () investigated the ultrasound‐assisted extraction of polyphenols from potato peels; they observed that time showed a significant positive effect on the extent of bioactive extraction and the rate of extraction was higher at the start of extraction time. Wang, Boussetta, Lebovka, and Vorobiev () observed that the initial portions of extracts was richer in catechin content as compared with last portions of extracts obtained using the long duration of ultrasound‐assisted extraction in ethanol/water mixtures. The previous literatures indicated that the extraction time is an important factor for the extraction of ingredients from plant materials.…”
Section: Resultsmentioning
confidence: 99%
“…The phenolic compounds present in the plant‐based foods have been proposed as food supplements for the management of type 2 diabetes mellitus due to their promising antioxidant and hypoglycemic effect reported in various in vitro, in vivo researches and clincial trials (Lin et al, ). The recent increasing trend of research to produce novel plant food products rich in phenolic compounds, such as Tartary buckwheat flour (Liu, He, Wang, & Wang, ), lettuce waste flour (Plazzotta, Sillani, & Manzocco, ), pomegranate peel extract chewing gum (Palabiyik et al, ), jambolan (Singh, Singh, Kaur, & Singh, ), and apple pomace (Wang, Boussetta, Lebovka, & Vorobiev, ) may suggest the role of plant‐based foods in human health.…”
Section: Introductionmentioning
confidence: 99%
“…The recent increasing trend of research to produce novel plant food products rich in phenolic compounds, such as Tartary buckwheat flour (Liu, He, Wang, & Wang, 2018), lettuce waste flour (Plazzotta, Sillani, & Manzocco, 2018), pomegranate peel extract chewing gum (Palabiyik et al, 2018), jambolan (Singh, Singh, Kaur, & Singh, 2018), and apple pomace (Wang, Boussetta, Lebovka, & Vorobiev, 2018) may suggest the role of plant-based foods in human health.…”
Section: Introductionmentioning
confidence: 99%
“…Results of many scientific researches pointed out positive effects of ultrasound, whether applied as pretreatment or treatment, on nutritional quality of food commodities, especially for fruit and vegetable-based products (Abid et al, 2013;Chemat, Zill-e, & Khan, 2011;Sae-leaw & Benjakul, 2018;Wang, Boussetta, Lebovka, & Vorobiev, 2018). Ultrasound is recognized as extremely effective processing method, and unlike thermal treatments, tends to have no significant losses of BACs.…”
mentioning
confidence: 99%